Stress Modeling of the Theistareykir Geothermal Area: Mapping of In-Situ and Deformation Event Stress Changes at an Active Geothermal Production Area in NE-Iceland - Kyle Robert Dawson 1996- (2022)
The evolution of rock-stresses within and around geothermal reservoirs can have important implications for the evolution of fluid flow in geothermal systems. While countrywide stress models for Iceland are available, a detailed stress change model of the Theistareykir Geothermal Area in NE Iceland has never been compiled. In this thesis, a stress change model of the Theistareykir Geothermal Area was developed containing stress change contributions from plate spreading and volcanic sources applied to faults and fractures with varied orientations (i.e. strike, dip, rake). The deformation in the model was compared with GNSS measurements, and borehole breakout measurements were used to verify the governing fault and stress orientations at depth. Further modeling was performed to determine the stress changes due to deformation events in the region, such as a major earthquake on the Húsavík-Flatey Fault, dike intrusions, rifting, or volcanic uplift, to determine the future impact they could have on the Theistareykir geothermal area. Our model shows that plate motion governs the annual stress changes in the area. The model results show that N-S trending normal faults are highly susceptible to receiving positive Coulomb stress change. Modeling of potential scenarios predicts that future deformation events could drastically alter the stress in the Theistareykir Geothermal Area. Stress change modeling along the Tjarnarás fault matches seismicity in the pre production period. In this study, the in-situ and future stress changes of the Theistareykir Geothermal Area were estimated. The method can easily be adapted to other geothermal locations worldwide. Future studies can build built upon this work for use in well placement, seismicity studies of production areas, fault movements, and as supplementary work for further numerical reservoir models. Keywords: Theistareykir, Geophysics, Geothermal, Stress Landsvirkjun